Salivary tumor marker CA15-3 and selected elements in relation to oral health status among a group of breast cancer women - Azeez, Basma A; Mohammed, Ahlam T (Journal of Baghdad College of Dentistry, 2015)
Background: Breast cancer is the commonest type of malignancy worldwide and in Iraq. It is a serious disease that affects the general health and cause systemic changes that affect the physical and chemical properties of saliva leading to adverse effects on oral health. This study was conducted toassess the tumor marker CA15-3 and selected elements in saliva and their relation to oral health status among breast cancer patients compared to control group. Materials and Methods: The total sample consisted of 60 women aged 35-45 years. 30 women were newly diagnosed with breast cancer before taking any treatment and surgery (study group) and 30 women without clinical signs and symptoms of breast cancer as a control group. Dental caries was recorded using DMFS index of WHO1987, andperiodontal parameters which include plaque index (PlI), calculus index (CalI), gingival index (GI), and Ramfjod index for the loss of periodontal attachment (CAL) were recorded.Stimulated salivary samples were collected and salivary flow rate, salivary CA15-3 and selected elements were determined. Results: Caries experience (DMFS) was higher among the study group compared with the control group but the difference was statistically not significant.The mean values of plaque index, calculus index, gingival index and loss of attachment were higher among the study group than the control group with a highly significant difference(P